PENGARUH CONTENT MARKETING TERHADAP CUSTOMER ENGAGEMENT DAN KEPUTUSAN PEMBELIAN PRODUK AVOSKIN YOUR SKIN BAE SERIES DI TIKTOK SHOP(STUDI PADA KONSUMEN DI KOTA MEDAN) - Sonnia Appriliani Rizki; Hafiza Adlina (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
86% of Indonesians have shopped on social commerce with 46% of transactions made through TikTok Shop. TikTok Shop is in great demand because it is considered by consumers to make online shopping activities easier while interacting with sellers without using other additional applications. One of the products that many consumers buy is beauty products, such as skincare. Therefore, the skincare industry has great potential to grow in the future. The purpose of this research was to analyze the effect of content marketing on customer engagement and consumer purchasing decisions on Avoskin Your Skin Bae Series products in Medan City. The effect of content marketing is analyzed by path analysis on customer engagement and purchasing decisions. The form of this research is quantitative research with an associative approach. The sampling method used purposive sampling with a sample size of 100 respondents. Primary data used in this research were obtained by distributing questionnaires while secondary data were obtained through literature studies. The data analysis methods used are descriptive analysis, validity test, reliability test, classical assumption test, path analysis, and hypothesis test. The results of this research showed that content marketing (X) has a direct positive effect on the customer engagement (Z) by 75,5%. The customer engagement (Z) has a direct positive effect on the purchasing decision (Y) by 46,3%. Content marketing (X) has a direct positive effect on the purchasing decision (Y) by 51,3% and a positive indirect effect of 34.9% through customer engagement, so it has 86.2% of the total effect